Tatak Pilipino [episode no. 87]. ([Quezon City ABS-CBN, 1992)
A unique display of Pilipino ways and style.
Philippine aso (10 min.) -- Rap music-Ngiti (3 min.) -- Juan Luna's cursed paintings (5 min.) -- Tektites (5 min.) -- Rap music-Harana (2 min.) -- Alalay sa artista (10 min.) -- Tambuli (3 min.) -- Smokey mountain in Tondo, Manila (2 min.) -- Sing along using Keraoke (5 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Luna, Juan; Dogs -- Philippines; Rap Music; Tektite -- Philippines; Tambuli; Employees -- Philippines; Audiocassettes